Impact of Mixed Farming on the Socioeconomic Conditions of Small-Scale Farmers in Tehsil Mankera District, Bhakkar - Draz, Umar; Waseem, Liaqate Ali; Ayub, Muahammad; Farhat, Komal (Pakistan Journal of Humanities and Social Sciences, 2023)
The research study investigates the mixed farming attributes of farmer's households concerning socioeconomic conditions and services provided in the study area. The baseline survey was executed to investigate the indigenous farming activities, socioeconomic conditions of the local community, and services provided in Tehsil Mankera, District Bhakkar. 200 farmers' households from 20 stations and eight union councils were selected for the baseline survey. Ten farmers' households from each village were selected with random sampling. The results revealed that the study area comprised three types of cultivation: tube well cultivation was 17%, canal cultivation was 4%, and rain-fed cultivation was about 79. The total cultivated area was 88%, and significant Rabi crops were Gram (the primary source of their livelihood), wheat (the local staple food of the farmers) with fodder like alfalfa and mustard. The main Kharif crops were pearl millet (bajra) and cluster bean (guar seed). The farmer's households have an average of 2-6 cattle at home. The area is mainly rain-fed with poor health, education, water, sanitation, and electricity facilities. Most of the farmers' households' land is under 5-10 acres with poor quality that is difficult to cultivate. Poverty prevails in the study area. Agriculture and livestock herding are their livelihood strategies. Expenditures are far more than the annual income of farmer's households. Farmer's households live below the poverty line.